Connection Knowledge and Attitude Mother to Giving Breastfeeding Compound Food in Infants Aged Less Than 6 Months in Region Kawatuna Public Health Center, Palu City - Andi Mariani; Niwayan Sridani; Fauzan Fauzan; Ratna Devi; Hayati Palesa (International Journal of Health and Social Behavior, 2025)
Background: Providing complementary foods too early for infants under 6 months of age is an indicator that the mother has failed to provide exclusive breastfeeding, which has an impact on the low coverage of exclusive breastfeeding. The purpose of this study was to determine the relationship between maternal knowledge and attitudes towards providing complementary foods for infants under 6 months of age in the Kawatuna Health Center Work Area, Palu City.Method: This type of research is descriptive research. The method used is a descriptive correlational method which is a study that is directed to explain the relationship between two variables. Namely the independent variable with the dependent variable. The number of samples is 26 using the Slovin formula. Data collection uses a questionnaire.Results: The results of the study showed that 26 respondents. Mothers with good knowledge were 6 respondents (26.0%) in good maternal attitudes where maternal knowledge is an important aspect of good growth and development and mothers with good knowledge about maternal attitudes will fulfill the provision of Complementary Food for Breast Milk Well while mothers with less knowledge were 7 respondents (49.7%).Conclusion: This study states that there is a relationship between knowledge and attitudes of mothers regarding the provision of Complementary Foods in the Kawatuna Work Area. The results of the chi square test analysis show that the P value = 0.000 because the P value ≤ 0.05 then Ha is accepted and H₀ is rejected, meaning that there is a relationship between knowledge and attitudes of mothers.